Obtenção de isolados a partir de recursos biológicos do bioma Pampa com potencial no controle de plantas daninhas - Souza, Angélica Rossana Castro de (2015)
The production of a bioherbicida for the biological control of weeds requires the development of a series of steps ranging from the selection of a suitable microbial strain for the production of product having herbicidal action until final formulation. Thus, this study aimed to select microorganisms from biological resources of the Pampa biome with potential for producing phytotoxins. Systematic samplings were performed with infectious symptoms in rice-growing areas and natural pastures of the Pampa biome. The first stage of the research was to select isolates with pathogenic potential inhibition test plants seedlings (Cucumis sativus L. var wisconsin.). The fungus that showed the best inhibitory effect was the VP51, identified through the use of molecular biology techniques, classified as Diaporthe sp. For optimization studies by means of submerged fermentation, industrial waste corn steep liquor were used (AMM) and sorghum (MAS), compared to synthetic medium. The means of submerged fermentation industry (AMM) showed better growth of fungal biomass and effect on test plant germination. In submerged fermentation bioreactor STR type, the rotation effect is significant, and the best results were obtained in tests with less rotation. In the pre-germination tests plants dormant and hard seeds were recorded, with a satisfactory result as biocontrol potential germination.